Physiological and Transcriptomic Analysis of Two Types of Hami Melons in Low-Temperature Storage - Wanqin Liao; Linlu Xiao; Xiangshuai Hao; Chunhui Shan; Zhongkai Zhou; Ming Ning; Fengxian Tang (Plants)
The Hami melon is a characteristic economic crop in Xinjiang. Long-term storage at low temperatures can cause cold damage and significantly impact the storage quality of Hami melon fruits. This study investigated the cold resistance of two Hami melon varieties under low temperatures, screened key genes, and further explored their resistance mechanisms. By comparing and analyzing the relationship between phenotypic morphology, physiological indicators, and storage time, it was found that the symptoms of cold damage in Hami melons are related to both storage time and variety. To analyze the response mechanisms of Hami melons to cold stress at the molecular level, we conducted transcriptome sequencing analysis on the cold-sensitive Hami melon variety Gold Queen and the cold-resistant variety Jia Shi. The analysis shows that cold stress induces the expression of these differentially expressed genes, which participate in the AsA-GSH cycling system, form the NADPH-P450 pathway, and establish the ERF-WRKY cold resistance pathway. This, in turn, increases the content of free proline in the fruits, clears denatured proteins within the fruit, maintains the stability of the redox system, and inhibits certain differentially expressed genes that regulate cell wall metabolism, thereby alleviating fruit softening and improving cold resistance.